Scenic wealth of biosphere reserve: valuing cultural ecosystem services using hedonic pricing - Mežgaile, Anda; Klepers, Andris (Landscape Architecture and Art, 2025)
This research uses the hedonic pricing method to explore the economic valuation of cultural ecosystem services (CES). North Vidzeme Biosphere Reserve, located in Latvia, has been used as a case study site. This vast area, with its diverse ecosystems, is crucial for studying CES due to its unique ecological and cultural significance as well as its interaction with human settlements. CES, including recreation, aesthetic appreciation, and cultural heritage, contribute to human well-being but are underrepresented in economic valuation and can be utilised in decision-making, especially in decisions regarding development alternatives. This study uses real estate transaction data and geographical information systems (GIS) to analyse how proximity to natural and cultural amenities influences property values. The research variables include structural attributes (e.g., property size and age), environmental factors (e.g., distance to waterbodies, coastlines, or nature trails), and neighbourhood landscape characteristics. Hedonic pricing models reveal that properties near natural amenities, such as coastlines and nature trails, exhibit higher valuations, reflecting the premium on access to CES and the potential for higher usage. Key findings include significant positive correlations between property prices and proximity to CES-rich environments, underscoring their role in shaping market perceptions and economic behaviors. However, the study highlights areas of concern, such as data limitations and methodological complexities, in isolating the specific impacts of CES. This interdisciplinary research provides empirical evidence for integrating CES into sustainable land-use planning and policy-making. By quantifying the economic benefits of CES, it advocates for enhanced recognition and preservation of these services, thereby balancing ecological conservation with socio-economic development.